2021
DOI: 10.1177/03000605211004702
|View full text |Cite
|
Sign up to set email alerts
|

Primary squamous cell carcinoma of the thyroid: a case report

Abstract: Primary squamous cell carcinoma of the thyroid (PSCCT) is a rare and rapidly progressive malignancy that carries a poor prognosis. PSCCT is easily misdiagnosed as acute thyroiditis or as another thyroid malignancy. We have reported a 76-year-old woman who presented with progressive neck pain for 1 month. Thyroid function tests revealed subclinical thyrotoxicosis. Ultrasound disclosed a solid nodule with calcification in the right thyroid lobe. Laboratory findings included neutrophilic leukocytosis and an eleva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Recently, it has been reported that S-100A9 is a marker of squamous cell origin and is diffusely expressed in thyroid squamous cell carcinoma and undifferentiated carcinoma with squamous cell components, while it is only scattered and focally expressed in CASTLE, which is helpful for the differentiation between them ( 12 ). Thyroid squamous cell carcinoma and undifferentiated carcinoma have a high degree of malignancy and are treated differently from thymoid-differentiated carcinoma ( 18 , 19 ). The different diagnosis and treatment processes for patients will directly affect the prognosis of patients, so it is particularly important to distinguish them.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been reported that S-100A9 is a marker of squamous cell origin and is diffusely expressed in thyroid squamous cell carcinoma and undifferentiated carcinoma with squamous cell components, while it is only scattered and focally expressed in CASTLE, which is helpful for the differentiation between them ( 12 ). Thyroid squamous cell carcinoma and undifferentiated carcinoma have a high degree of malignancy and are treated differently from thymoid-differentiated carcinoma ( 18 , 19 ). The different diagnosis and treatment processes for patients will directly affect the prognosis of patients, so it is particularly important to distinguish them.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in any patient with a known history of tumors, one should be alert to the potential risk of metastasis when a new thyroid mass is present. The location of the mass may provide a guide to the location of the primary tumor ( 15 ).…”
Section: Originmentioning
confidence: 99%
“…The likely primary site can be determined by reviewing the patient’s medical history and physical examination, but a whole-body exam may also be required ( 15 ).…”
Section: Clinical Signsmentioning
confidence: 99%
See 2 more Smart Citations